RANCANG BANGUN LOKALISIR GANGGUAN SALURAN KABEL TEGANGAN MENENGAH (SKTM) BERBASIS SMS - Abdul Hadi; Mochamad Susantok (ABEC Indonesia, 2021)
Medium Voltage Cable Line (SKTM) is a 20,000 volt cable that is installed underground to avoid roads, enter buildings owned by PLN customers, and avoid electrical hazards to the public. The number of SKTM points in the PT PLN (Persero) Unit, especially the ULP Bagan Batu, makes it difficult for workers to find the location of the disturbance caused by the SUTM or SKTM network itself. If there is a disturbance, SKTM, which is damaged, the localization process and electrical normalization will take longer. So it is necessary to make a device by attaching a current sensor at the input and output end of each SKTM in order to determine the location of the affected SKTM or SUTM. The impulses read by the current sensor will be managed by Arduino Mega 2560 which will then be notified via an SMS gateway. This system performance resulting about 5 sec delay transmission data to smartphone and sensor accuracy 1,83%. It is hoped that this design can solve the tracking problem more easily and quickly so that PT PLN customers do not feel the outages for too long and as a reference for PT PLN makes their equipment to the 20,000 volt working system.